PENERAPAN MODEL INTEGRASI DALAM RESOURCES-BASED VIEW SEBAGAI STRATEGI BERSAING PERUSAHAAN DALAM PANDANGAN ISLAM - BUDI GAUTAMA SIREGAR (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2016)
Jay Barney (1991) developed the concept of resource-based view which has an important role for strategic management. The concept states that the organization will achieve sustainable competitive advantage if it has a valuable resource, unique, rare and difficult to imitate. Resource-based view emphasizes the internal factors of the organization and criticized the approach of industrial organization that emphasizes the organization of external factors.  Based on the resource-based view, organizations can determine the strategy to be done in accordance with the capabilities of the organization. However, resourcebased view also has some disadvantages particularly with regard to conceptual issues and issues of research methods. This article discusses these issues and possible integration of resource-based view with the approach of industrial organization